Der Franziszeische Kataster im Kronland Bukowina. Czernowitzer Kreis (1817-1865) Statistik und Katastralmappen - Scharr, Kurt (2015)
The Bukovina is the first crown land of this edition project situated completely outside today's Austrian territory. On the basis of the land register of Francis I and using a proven analytic method, this volume is the first systematic edition of comprehensive sources of social, economic and societal history for an entire region and makes them available for further research.